Training In Making Supplementary Foods and Stunting Prevention Education Through Android-Based â€œAnak Sehatâ€ Digital Application at Kelurahan Petapahan, Lubuk Pakam Sub-District, Deli Serdang Regency - Eka Nugraha, Sony; Marianne; Keliat, Jane Melita (Talenta Publisher, 2023)
Teaching, carrying out research for the development of science and applying knowledge, all three of which form a single unit known as the Tridharma of Higher Education. Community service is the third dharma of the Tridharma of Higher Education. The existence of community service is actually very important both for the management of the tertiary institution as well as for the existence of the tertiary institution in the community. The community service carried out is